Analisis Pemanfaatan Energi Panas Menjadi Energi Listrik Pada Proses Pengereman Rem Cakram Pada Kendaraan Roda Empat - Calvin Hans Adam Calvin; Erlanda Augupta Pane (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2020)
This research was conducted to determine the electrical energy generated from friction heat in the braking process of disc brakes on four-wheeled vehicles with a calculation analysis of heat flow rates at speeds of 10 km/h and 15 km/h at 519 rpm, 748 rpm, and 1.234 rpm. The testing time is 20 minutes to get a measure of the heat generated from braking friction. The heat produced is converted into electrical energy using a thermoelectric device. Based on the calculation of the heat flow rate caused by friction on braking, a heat flow rate of 141.61 Watt is obtained and the voltage result is 317.2 mV. These results indicate the longer the braking is done, the heat generated from the friction force, the rate of heat flow flowing from the disk to the thermoelectric device, and the voltage result will be greater.